Analyzing Student Retention Trends in Public Schools Across Kwara State Nigeria - Shittu, Afeez Adeshina; Sheu, Muritala Adaramaja; Faruk, Yusuf Abubakar (EDUCARE: Journal of Primary Education Published by Faculty of Tarbiyah and Teacher Training, Kiai Haji Achmad Siddiq State Islamic University of Jember, East Java, Indonesia, 2025)
This study investigated the assessment of students’ retention rate in public junior secondary schools in Kwara State, Nigeria. The study specifically sought to examine the retention rate of the public junior secondary school students in Kwara State from 2013/14 to 2019/2020 based on gender, and investigate the retention rate of the public junior secondary school students in Kwara State from 2013/14 to 2019/2020 based on location. Two research questions were raised and answered to guide this study, while two hypotheses were formulated and tested at the 0.05 significance level. The study was a descriptive survey that adopted the correlational research design. The target population comprised all 230 public junior secondary schools in the 6 LGA selected from the three senatorial districts in Kwara State. The instrument for this study was the Students’ Flow Checklist (SFC). The data collected were analysed using the formula, standard progression method, rate method, and t-test. The findings revealed a significant difference in the retention rates of male and female students in Ilorin West and Asa LGA in public junior secondary schools in Kwara State. There was a considerable difference in the retention rates of students in Ilorin West LGA (Urban) and Asa LGA (Rural) in public junior secondary schools in Kwara State. It is recommended that retention rates in Kwara State’s public junior secondary schools be maintained by providing more classrooms, utilizing available resources, and ensuring effective teaching to achieve educational goals for all students.